2021
DOI: 10.3390/microorganisms9061148
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Antimicrobial Resistance and Virulence Genes of Bacterial Pathogens from Bovine and Caprine Mastitis in Northern Lebanon

Abstract: Mastitis is an infectious disease encountered in dairy animals worldwide that is currently a growing concern in Lebanon. This study aimed at investigating the etiology of the main mastitis-causing pathogens in Northern Lebanon, determining their antimicrobial susceptibility profiles, and identifying their antimicrobial resistance (AMR) genes. A total of 101 quarter milk samples were collected from 77 cows and 11 goats presenting symptoms of mastitis on 45 dairy farms. Bacterial identification was carried out t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Liu et al (2018) from China reported 09.60% E. coli isolates from pigs as ESBL producer harbored at least one type of beta lactamase, with bla CTX"M, bla TEM, being detected in 90.90% and 68.18%, respectively. Abboud et al (2021) investigated the etiology of the main mastitis causing pathogen and identified their antimicrobial resistance (AMR) ESBL gene, blaTEM in (83.3%) E. coli isolates.…”
Section: Genotypic Characterization Of Methicillin-resistant S Aureus...mentioning
confidence: 99%
“…Liu et al (2018) from China reported 09.60% E. coli isolates from pigs as ESBL producer harbored at least one type of beta lactamase, with bla CTX"M, bla TEM, being detected in 90.90% and 68.18%, respectively. Abboud et al (2021) investigated the etiology of the main mastitis causing pathogen and identified their antimicrobial resistance (AMR) ESBL gene, blaTEM in (83.3%) E. coli isolates.…”
Section: Genotypic Characterization Of Methicillin-resistant S Aureus...mentioning
confidence: 99%
“…In the case of livestock animals, MDR bacteria may enter the food chain and thus be responsible for AMR spread. Abboud et al sought to investigate the etiology of the main mastitis-causing pathogens in northern Lebanon, determine their antimicrobial susceptibility profiles, and identify their antimicrobial resistance (AMR) genes [ 19 ]. A total of 101 quarter-milk samples were collected from 77 cows and 11 goats presenting symptoms of mastitis on 45 dairy farms.…”
mentioning
confidence: 99%